Evaluasi Good Corporate Governance atas Kebutuhan Donatur pada Penerapan Crowdfunding di Indonesia: Studi Kuantitatif dan Kualitatif pada Efekrumahkaca.Net, Patungan.Net, dan Wujudkan.Com - Tirdanatan, Nia Utami; Georgiana, Vina; Sun, Yen (ComTech: Computer, Mathematics and Engineering Applications, 2014)
This research aims to evaluate the implementation of Good Corporate Governance (GCG) in ensuring the good management of crowdfunding entities in Indonesia. Research methodology is using both quantitative and qualitative approaches. Quantitative approach was conducted by analyzing the factors of the driving forces for donors in financially participating in crowdfunding initiatives. Conceptual framework is developed and a study was conducted to 96 donors from three Indonesian crowdfunding portals. The findings of quantitative study show that the main factor that drive the donors to participate is motivation to accomplish, social merit factors and good trust to the project creator. Based on that results, qualitative study was conducted to evaluate the implementation of Good Corporate Governance (GCG) principles in those three Indonesian crowdfunding portals. The evaluation explains that GCG principles has been well implemented by those administrators of crowdfunding portals. Nevertheless, serious concern should be taken in the area of accountability and financial reporting. The research provides insights for crowdfunding practitioners to be succesfully raise funding and for crowdfunding platforms to be sustainable in this business by implementing good corporate governance. This research takes a further step in explaining crowdfunding phenomenon in Indonesia.